The New York colony - Fradin, Dennis B. (Chicago, Ill. : Childrens Press, 1988)
This book traces the history of the Dutch colony beginning with the years it was inhabited only by Indians to the time it became the eleventh state.
Includes index.
Includes chronology.
Keywords: New York (State) -- History; New York (State) -- Biography